2017
DOI: 10.1159/000479460
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Prenatal Testing for Sex Chromosome Aneuploidy in Routine Clinical Practice

Abstract: Objectives: To assess the accuracy of non-invasive prenatal testing (NIPT) for sex chromosome aneuploidy (SCA) in routine clinical practice and to review counselling and sonographic issues arising in SCA cases. Methods: Three specialist Australian obstetric ultrasound and prenatal diagnosis practices offering NIPT after 10 weeks' gestation participated in this study. NIPT was reported for chromosomes 21, 18, 13, X, and Y. Results: NIPT screening was performed in 5,267 singleton pregnancies. The odds of being a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 20 publications
10
36
0
Order By: Relevance
“…All these findings highlight the critical need for comprehensive pretest and posttest counseling provided by a multidisciplinary team having specific knowledge about the detailed features of each syndrome, as suggested by multiple studies . Medical geneticist have a central role not only for counseling about prenatal diagnosis but also for postnatal follow‐up.…”
Section: Invasive Prenatal Diagnosis Rate and Confirmation Rates Of Nmentioning
confidence: 95%
“…All these findings highlight the critical need for comprehensive pretest and posttest counseling provided by a multidisciplinary team having specific knowledge about the detailed features of each syndrome, as suggested by multiple studies . Medical geneticist have a central role not only for counseling about prenatal diagnosis but also for postnatal follow‐up.…”
Section: Invasive Prenatal Diagnosis Rate and Confirmation Rates Of Nmentioning
confidence: 95%
“…While SCAs as a group are as common as autosomal aneuploidies in low‐risk populations, NIPT performance is not as good for SCAs as compared to trisomies 21, 18, and 13 because of fetal mosaicism, confined placental mosaicism, underlying maternal X chromosome variation, and/or fetal aneuploidy diagnoses outside the scope of NIPT validation . The majority of the published data regarding positive and negative predictive values comes from commercial labs in addition to a few retrospective studies from clinical practices . These prior case series have shown that inclusion of SCAs on NIPT platforms doubles the overall positive screening rate and increases the false positive rate .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the published data regarding positive and negative predictive values comes from commercial labs in addition to a few retrospective studies from clinical practices . These prior case series have shown that inclusion of SCAs on NIPT platforms doubles the overall positive screening rate and increases the false positive rate . The true positive rate for monosomy X especially is much lower as compared to autosomal trisomies most likely because of maternal and placental mosaicism …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonosomal aberrations are theoretically exposed during NIPT in a similar way as any other aneuploidy. Nevertheless, the specificity is reported to be much lower in comparison with traditional screening of chromosomes 13, 18, and 21, especially for monosomy X . Ethical issues on reporting these sometimes nonsevere abnormalities aside, the incorporation of FF in statistical outcome—which is generally not done with, eg, the popular z ‐score approach—does improve performance .…”
Section: Discussionmentioning
confidence: 99%